m = 1 ∑ ∞ ( m 2 + m ) ( m 4 + m 2 + 1 ) m 3 + ( m 2 + 1 ) 2
If the series above can be expressed as B A for coprime positive integers A and B , find the value of A + B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great telescoping sum approach.
How can one motivate this?
Challenge Master: Well, basically it's a sum of many terms, it's common to consider Telescoping Sum as a viable approach. If this is not possible, then I may need devise other techniques to solve this. For example, n = 1 ∑ ∞ n 2 + 1 1 is not solvable by Telescoping Sum, so I may consider Riemann Sum or some other more advanced approach.
TL;DR: Always try telescoping sum first.
Well done!
Log in to reply
THANK YOU!
Log in to reply
nice solution
HENCE 1.5 that is 3/2 i.e 3 + 2 =5
Please provide a complete solution explaining the steps that you did.
Do not simply use a computing device without understanding the work that is involved.
Problem Loading...
Note Loading...
Set Loading...
We begin by rearranging the numerator of the given fraction, m 3 + ( m 2 + 1 ) 2 = ( m 4 + m 2 + 1 ) + ( m 3 + m 2 ) .
So ( m 2 + m ) ( m 4 + m 2 + 1 ) m 3 + ( m 2 + 1 ) 2 = m ( m + 1 ) 1 + m ( m + 1 ) ( m 4 + m 2 + 1 ) m 2 ( m + 1 ) = m 1 − m + 1 1 + m 4 + m 2 + 1 m .
Note that we can factorize m 4 + m 2 + 1 to ( m 2 − m + 1 ) ( m 2 + m + 1 ) .
By partial fraction, we get m 4 + m 2 + 1 m = 2 1 ( m 2 − m + 1 1 − m 2 + m + 1 1 ) .
Denoting a m = m 2 + m + 1 1 , then a m − 1 = m 2 − m + 1 1 . By telescoping sum,
= = m = 1 ∑ ∞ ( m 2 + m ) ( m 4 + m 2 + 1 ) m 3 + ( m 2 + 1 ) 2 m = 1 ∑ ∞ [ ( m 1 − m + 1 1 ) + 2 1 ( a m − 1 + a m ) ] 1 1 + 2 1 a 0 = 2 3